Post-harvest Application of Methyl Jasmonate or Prohydrojasmon Affects Color Development and Anthocyanins Biosynthesis in Peach by Regulation of Sucrose Metabolism - Tang, Tingting; Zhou, Hongsheng; Wang, Libin; Zhao, Jing; Ma, Lijie; Ling, Jun; Li, Guofeng; Huang, Wen; Li, Pengxia; Zhang, Yingtong (Frontiers in Nutrition, 2022)
The roles of methyl jasmonate (MeJA) and prohydrojasmon (PDJ) in postharvest color development and anthocyanins biosynthesis in the skin of peach fruit remain unclear. In this study, peach fruit were infiltrated with MeJA (200 μM) or PDJ (40 μM) and stored at 22°C for 7 days. The results showed that treatment with MeJA or PDJ had a positive effect on red color formation in peach fruits due to anthocyanins accumulation (~ 120% increase). This was attributed to increased enzyme activities, and enhanced transcript abundance of the genes associated with anthocyanins biosynthesis, induced by MeJA or PDJ. Both MeJA and PDJ promoted sucrose biosynthesis, and the subsequently elevated levels of the sucrose during storage were positively correlated with anthocyanins accumulation (0.49) and the activities of key biosynthesis enzymes (0.42-0.79). Based on these findings, we proposed that MeJA or PDJ treatments promote anthocyanins biosynthesis by regulating sucrose metabolism during the postharvest storage of peach fruit.